Peningkatan Kemampuan Motorik Halus Melalui Teknik Mozaik pada Siswa Tunagrahita Kelas 1 di SLB Citra Mulia Mandiri Yogyakarta - Hasbi Arsanti; Krida Singgih Kuncoro (WACANA AKADEMIKA: Majalah Ilmiah Kependidikan, 2022)
This study aims to improve the fine motor skills of students with intellectual disability through mosaic techniques. This study is action research with subjects in the 1st-grade student with intellectual disability in SLB Citra Mulia Mandiri in the 2020/2021 academic year. The action in this research is a cyclical model. The data was collected through observation and documentation. The research instrument employed an observation guide. Data analysis technique was used descriptive qualitative. The results showed that the process of learning the mosaic technique can improve the fine motor skills of students with intellectual disability in the 1st grade. The learning process of the mosaic technique also increases students' concentration, independence, and ability to differentiate shapes (e.g., semi-circle, circle, quadrilateral, and triangle geometric shapes).